Відприслівникова дієслівна аналітична синтаксична транспозиція на тлі інших різновидів дієслівних переходів - Мельник, Ірина Анатоліївна; Melnyk, Iryna (Східноєвропейський національний університет, 2013)
Досліджено вплив семантики прислівників на можливість/неможливість їхнього переходу в синтаксичну сферу дієслова; визначено параметри вживання прислівників у позиції складеного прислівникового присудка двоскладних речень і позиції співвідносного з присудком головного члена односкладних речень; виявлено морфологічну експлікацію підмета, пов’язаного із зазначеними типами присудків. This article deals with the integral analysis of the peculiarities of adverb transposition into syntactic sphere of the verb compared with other types of verbal transitions, in particular the impact of adverbs in positive and comparative/superlative degrees semantics on possibility/impossibility of syntactic transition into verbal formal-syntactic predicate position is defined; the qualitative composition of analytical syntactic morphemes – connectives and semi-connectives – is determined and their role in adverbial verbal analytical syntactic transposition is characterized; parametres of using adverbial verbal analytical syntactic transpozits in the position of the compound adverbial predicate in two-member elementary and non-elementary sentences and in the position of the main member of a one-member impersonal sentence, correlative with the predicate, are defined; morphological explication of the subject, combined with the types of predicats, stated above, is analysed.
Adverbial Verbal Analytical Syntactic Transposition Compared with other Types of Verbal Transitions
Keywords: відприслівникова дієслівна аналітична синтаксична транспозиція; означальні прислівники; обставинні прислівники; аналітична синтаксична морфема-зв’язка; аналітична синтаксична морфема-напівзв’язка; відприслівниковий дієслівний аналітичний синтаксичний транспозит; прислівниковий складений присудок; співвідносний з присудком головний член односкладних речень; типова й нетипова форми вираження підмета; adverbial verbal analytical syntactic transposition; defining adverbs; adverbs as adverbial modifiers; analytical syntactic morpheme- connective; analytical syntactic morpheme-semi-connective; adverbial verbal analytical syntactic transpozit; adverbial compound predicate; the main member of a one-member impersonal sentence correlative with the predicate; standard and non-standard ways of expressing the subject